Pelatihan Penyusunan Proposal Acara (Event) di Desa Wisata Panji, Kabupaten Buleleng, Bali - Suprastayasa, I Gusti Ngurah Agung; Wirata, I Nengah; Citrawati, Luh Putu; Sumadi, I Gede; Ariasri, Nyoman Reni (Jurnal Pemberdayaan Pariwisata, 2024)
Panji Tourism Village is located in Sukasada District, Buleleng Regency, Bali. This village has an activity called the Panji Festival held before the Covid-19 pandemic. Since the pandemic, the Panji Festival could not be held. T he Festival was usually executed by  a third party. Therefore, through coordination communication between the Village Head and the Convention and Event Management Study Program, a training activity was carried out with the aim of improving the ability of youth and the Village community to prepare event proposals. The training activity was carried out on November 9-10, 2023 with a lecture approach, group discussions and group presentations. The training activity went well and produced three event proposals that were ready to be submitted to various related parties. The participants felt that this activity was very useful and gave a positive assessment of the implementation of this training activity. Keywords:   events, banner festivals, training, preparation of proposals